2017
DOI: 10.1038/srep41115
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, TV Watching Time, Sleeping, and Risk of Obesity and Hyperglycemia in the Offspring of Mothers with Gestational Diabetes Mellitus

Abstract: We investigated the association of physical activity, TV watching time, sleeping time with the risks of obesity and hyperglycemia among 1263 offspring aged 1–5 years of mothers with gestational diabetes (GDM) in a cross-sectional study. Logistic regression models were used to obtain the odd ratios (ORs) (95% confidence intervals [CI]) of childhood obesity and hyperglycemia associated with different levels of indoor activity, outdoor activity, TV watching, and sleeping time. The multivariable-adjusted ORs of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…It is known that women with low levels of physical activity during pregnancy have a higher risk of developing GDM. 26,27 Approximately one-third of this sample of the LINDA-Brasil study was physically active; this is worrying considering the potential of this behavior to prevent development of T2D after delivery. In addition, physical activity improves glycemic control 8,10 and contributes to a reduction in weight gain in women diagnosed with GDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that women with low levels of physical activity during pregnancy have a higher risk of developing GDM. 26,27 Approximately one-third of this sample of the LINDA-Brasil study was physically active; this is worrying considering the potential of this behavior to prevent development of T2D after delivery. In addition, physical activity improves glycemic control 8,10 and contributes to a reduction in weight gain in women diagnosed with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Charts were reviewed to collect data on prepregnancy weight, gestational weight, gestational age at recruitment, plasma glucose levels at diagnosis of GDM, treatment for GDM, and reproductive history. 21,23 For descriptive analyses, age was classified into three categories (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and ≥40 years). Self-declared skin color was categorized as white, black, brown, or other, according to the Brazilian census bureau.…”
Section: Measurementsmentioning
confidence: 99%
“…While this finding was restricted to just two of the five adiposity measures, the point estimates for the remaining three adiposity outcomes follow a similar pattern. These results are in contrast to a large Chinese study, which observed no difference in obesity prevalence at 1 to 5 years of age for children exposed to GDM across higher or lower levels of indoor/outdoor physical activity . However, that study did not include a control group of children not exposed to GDM and thus could not determine if increased physical activity can ameliorate the adverse effect of GDM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the potential of other health behaviours in childhood to attenuate the obesity risks of this intrauterine exposure. One study of Chinese children exposed to GDM reported that those who did not watch television daily were less than half as likely to be obese compared with those who watched >1 hour daily . However, there was no difference in obesity risk according to physical activity, and diet was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one study has specifically measured the impact of lifestyle behaviors on obesity risk in children exposed to GDM in utero. In that study, Zhang and collaborators [71] showed that TV watching time > 1 h/day was associated with increased risk of obesity and central obesity in a population of children aged 1-5 years born from mothers with GDM in China. However, they found no association of indoor activity, outdoor activity, and sleeping time with the risk of obesity or central obesity [71].…”
Section: Dietary Intake and Physical Activity During Childhoodmentioning
confidence: 99%